THE PHENOMENON OF NOMINAL WORD FORMATION IN MEDICAL TERMINOLOGY (Modern education and development, 2025)
In this article, we briefly discuss the phenomenon of nominal word formation in the Latin language. As is known, the origin of medical terminology is also closely related to Greek lexical and word-formation resources. It is worth noting that since literary Latin has absorbed many elements of the Greek language, it has become not only the richest source for future terminological systems but also a mediator in supplementing these systems with Greek elements.